Analisa Metodologi Tafsir Al-Quran Berbasis Ormas di Indonesia Perspektif Metodologi Islah Gusmian - Nurun Najmatul Ulya; Ahmad Yasir Amrulloh (Jurnal test, 2023)
This article examines Indonesian commentary books compiled by Indonesian Community Organizations (ORMAS) or their representatives, namely Tafsir Al-Wa'ie Selected Verses by Hizbut Tahrir Indonesia and Tafsir At-Tanwir by Majlis Tarjih and Tajdid PP Muhammadiyah. The type of research method is library research, because the source of the analysis is based on library data, namely the work of interpretation by the two ORMAS and the formulation of the methodology developed by Islah Gusmian, "New Directions of Study Methodology on Al-Qur'an Interpretation." In particular, the 11 variables Gusmian analyzed to dissect Indonesian commentary works. Namely: (1) the systematic presentation of the interpretation (2) the form of presentation of the interpretation (3) the style of language in which the interpretation is written (4) the form of writing the interpretation (5) the nature of the commentator (6) the scholarship of the interpreter (7) the origins of the commentary literature (8) the sources reference sources (9) Interpretation method (10) nuances of interpretation (11) interpretation approach. After conducting a study of the two interpretations, it was concluded that the methodology used by these two ORMAS interpretation books has similarities and differences. The similarities can be seen in the systematic presentation of interpretations, forms of presentation, forms of writing, style of language, origins of literature, sources of reference, nuances of interpretation and approach. Meanwhile, the other three variables, namely the nature of the interpreter, the knowledge of the interpreter, and the method of interpretation show different results. For this reason, similar research can be developed to dissect the works of Archipelago interpretations in Indonesia, so that the methodology used will add variants to the treasures of Nusantara interpretation studies.